SMART LIVESTOCK FARMING UNTUK TINGKATKAN EFISIENSI USAHA PETERNAKAN DI KELOMPOK TERNAK KAMBING GAYUH MUKTI BANTUL - Zennul Mubarrok, Zennul Mubarrok; Ahmad Hanafi; Gaguk Marausna; Aris Wahyu Murdiyanto; Ikbal Rizki Putra; Almayanti Susillia Ningrum; Surya Rizki (Jurnal Berdaya Mandiri, 2025)
This Community Service Program aimed to improve business efficiency at the Gayuh Mukti Goat Farmers' Group in Bantul, Yogyakarta, which faced constraints in electricity supply, waste management, and feed processing. Through a participatory approach involving socialization, training, and assistance, three appropriate technologies were implemented to address these issues. The interventions included a feed chopper machine, a compost converter, and a solar panel installation equipped with a solar tracker. The implementation resulted in significant positive impacts: a 61.67% increase in feed chopping time efficiency; a 21.74% increase in organic fertilizer production self-sufficiency; and a 10% utility rate for the solar panel in providing emergency power during blackouts. In addition to the primary output of the technologies, this program also produced a scientific article accepted in a Sinta 4 accredited journal, mass media publications, and video content. This success provides a foundation for future sustainability programs focusing on agrotourism development and strengthening group management. Keywords: Community Service, Business Efficiency, Appropriate Technology, Goat Farming, Community Empowerment.